NAIP/NLRC4 inflammasome participates in macrophage responses to Trypanosoma cruzi by a mechanism that relies on cathepsin-dependent caspase-1 cleavage - Amaral, Marcelo Pires; Cardoso, Felipe Daniel; de Farias, Ingrid Sancho; de Souza, Rafael Queiroz; Matteucci, Kely Catarine; Torrecilhas, Ana Claudia; Bortoluci, Karina Ramalho (Frontiers in Immunology, 2023)
Inflammasomes are large protein complexes that, once activated, initiate inflammatory responses by activating the caspase-1 protease. They play pivotal roles in host defense against pathogens. The well-established role of NAIP/NLRC4 inflammasome in bacterial infections involves NAIP proteins functioning as sensors for their ligands. However, recent reports have indicated the involvement of NLRC4 in non-bacterial infections and sterile inflammation, even though the role of NAIP proteins and the exact molecular mechanisms underlying inflammasome activation in these contexts remain to be elucidated. In this study, we investigated the activation of the NAIP/NLRC4 inflammasome in response to Trypanosoma cruzi, the protozoan parasite responsible for causing Chagas disease. This parasite has been previously demonstrated to activate NLRP3 inflammasomes. Here we found that NAIP and NLRC4 proteins are also required for IL-1β and Nitric Oxide (NO) release in response to T. cruzi infection, with their absence rendering macrophages permissive to parasite replication. Moreover, Nlrc4-/- and Nlrp3-/- macrophages presented similar impaired responses to T. cruzi, underscoring the non-redundant roles played by these inflammasomes during infection. Notably, it was the live trypomastigotes rather than soluble antigens or extracellular vesicles (EVs) secreted by them, that activated inflammasomes in a cathepsins-dependent manner. The inhibition of cathepsins effectively abrogated caspase-1 cleavage, IL-1β and NO release, mirroring the phenotype observed in Nlrc4-/-/Nlrp3-/- double knockout macrophages. Collectively, our findings shed light on the pivotal role of the NAIP/NLRC4 inflammasome in macrophage responses to T. cruzi infection, providing new insights into its broader functions that extend beyond bacterial infections.